The Influence of Social Environment and Financial Literacy on Students' Financial Behavior With Fintech as a Moderation - Muhammad Saddam; Tsamarah Az Zahra; Muhammad Rifais (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2023)
This research aims to determine the influence of the social environment and financial literacy on student financial behavior and financial technology as a moderating variable. This research is a type of quantitative research with a total of 105 students at STIE Hidayatullah Depok as respondents. Data was obtained by distributing questionnaires using Google Form media. The sample was selected using criteria with a random sampling technique calculated using the Slovin formula. The data used is primary data in the form of respondents' answers and processed using SPSS version 26. The results of this research show that the social environment and financial literacy have a positive and significant effect on student financial behavior at STIE Hidayatullah Depok with financial technology as a moderating variable.